Low-Energy Electron Interactions with Radiosensitisers and Hydrated Biomolecular Clusters - Meissner, Rebecca (2020)
Interactions of free electrons with kinetic energies between 0 eV and 100 eV with isolated biomolecules, (hydrated) radiosensitisers and doped neon clusters were studied, with focus on associative and dissociative electron attachment (AA and DEA, respectively) processes and electron ionisation. Radiosensitisers are applied in radiotherapy to enhance the ratio of damage to malignant compared to healthy cells. The principle of action on a physico-chemical stage is yet unknown and was studied within this thesis. Clusters are an intermediate state of matter between gaseous and solid state. In this thesis, cluster size dependencies and effects in doped clusters were studied. Two different mass spectrometry setups were used. Data from electron interactions with both gas-phase biomolecules and doped neon clusters was taken at the experimental apparatus in Innsbruck. A hemispherical electron monochromator enables high energy resolution measurements and is combined with a quadrupole mass filter. For the acquisition of hydrated radiosensitiser data, the setup in Prague was used. There, an electron gun is combined with a time-of-flight mass analyser. The clusters were in both cases produced via supersonic expansion. The radiosensitisers studied include 5-selenocyanato-2’-deoxyuridine (SeCNdU), nimorazole and misonidazole. All of them exhibit efficient electron capturing characteristics. SeCNdU is a potential radiosensitiser for highly proliferating cells and exhibits (SeU-yl) and CN as strongest fragment anions upon DEA, formed already at virtually 0 eV kinetic energy of the incoming electron. The formation of highly reactive species reinforce SeCNdU as a promising candidate. Nimorazole and misonidazole both exhibit an intense ion signal for the parent anion upon electron attachment. The absolute cross section at 0 eV electron energy was determined for nimorazole and is in the order of 3 1018 m2. For misonidazole, the absolute cross section is estimated to be of the same order of magnitude. The fragmentation channels upon DEA are at least one order of magnitude weaker, with NO 2 being the most intense among them. They are further quenched upon hydration of the agent. It is suggested that the radiosensitising action is caused by the associative attachment channel and the DEA products only play a minor role, opposing previous assumptions. In case of the doped neon clusters, indications for the formation of a conduction band were found in the form of an energy barrier for incoming electrons: Comparing previous results of electron attachment to pure carbon dioxide clusters with neon clusters doped with CO2 results in a blue-shift of the resonance positions by up to 0.8 eV. The effect depends on the size of the neon cluster. For molecular oxygen as the dopant, evidence was found that an incoming electron can first react with the neon cluster via an excitation event and subsequently attach to the dopant cluster. Both the study of radiosensitisers and of neon clusters should be continued. Further radiosensitisers should be studied in order to implement a model in which the effects on a physico-chemical stage are investigated and compared to radiosensitisers already in use. From such a study, potential new radiosensitisers can be derived. In the study of doped neon clustes, the solvation of different complexes with neon was investigated. Particularly, the formation of a conduction band, neon cluster - dopant interactions, and quenching of molecular processes in dopants by neon as a collision partner are analysed. The results require further investigations of additional dopants to unambiguously explain those effects.